2022
DOI: 10.1111/1462-2920.16078
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of H2S from anaerobic thiolated ligand biodegradation rapidly generates bioavailable mercury

Abstract: Summary Methylmercury is a potent neurotoxin that biomagnifies through food webs and which production depends on anaerobic microbial uptake of inorganic mercury (Hg) species. One outstanding knowledge gap in understanding Hg methylation is the nature of bioavailable Hg species. It has become increasingly obvious that Hg bioavailability is spatially diverse and temporally dynamic but current models are mostly built on single thiolated ligand systems, omitting ligand exchanges and interactions, or the inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…8a), indicating that P. hydrargyri BerOc1 can degrade thiols such as cysteine to produce biogenic sulfides. Other strains, affiliated with E. coli and G. sulfurreducens, were also demonstrated to degrade cysteine and produce biogenic sulfides [26][27][28]. The presence of these biogenic sulfides could change the speciation of metals such as Hg in solution to form other Hg(II)-sulfide species.…”
Section: Sulfide and Cysteine Detection In The Culturementioning
confidence: 99%
See 2 more Smart Citations
“…8a), indicating that P. hydrargyri BerOc1 can degrade thiols such as cysteine to produce biogenic sulfides. Other strains, affiliated with E. coli and G. sulfurreducens, were also demonstrated to degrade cysteine and produce biogenic sulfides [26][27][28]. The presence of these biogenic sulfides could change the speciation of metals such as Hg in solution to form other Hg(II)-sulfide species.…”
Section: Sulfide and Cysteine Detection In The Culturementioning
confidence: 99%
“…The presence of these biogenic sulfides could change the speciation of metals such as Hg in solution to form other Hg(II)-sulfide species. Stenzler et al [27] demonstrated that exogenous biogenic sulfide, originating from anaerobic microbial thiol degradation, can alter Hg speciation; nanomolar levels of sulfides were sufficient to change Hg(II) speciation and form aqueous Hg(II)sulfides [i. e., Hg(HS) 2 and Hg(HS) − ] or facilitate the precipitation of metacinnabar (β-HgS(s)), resulting in an increased microbial Hg methylation.…”
Section: Sulfide and Cysteine Detection In The Culturementioning
confidence: 99%
See 1 more Smart Citation